Peranan Korban Dalam Terjadinya Kejahatan Seksual Terhadap Anak Ditinjau dari Perspektif Viktimologi - Evy Nurinayah I Wayan Wahyu Anandita (Universitas Muhammadiyah Metro, 2023)
Recently, crimes of sexual abuse against children have often occurred. Sex crimes among children stem from a number of circumstances, such as pornographic shows that are easily accessible recently, as well as the inability of victims of harassment to report perpetrators of sexual crimes that occur to children. Victims who were victimized did not dare to sue the perpetrators. The problem in this article is how the author views the role of the victim in sexual crimes. The methodology used in this review includes the use of a qualitative appr oach using sources from literature reviews, such as those related to the topics discussed. The conclusion from this study is that some child victims of sexual abuse may also have no clear symptoms. The effects of sexual harassment are very serious and can manifest in a variety of pathological symptoms and behaviors. There is almost no area of general symptoms that is not related to a history of sexual abuse. Age and various abuse-related factors can influence the nature and severity of symptoms.